The effect of inquiry learning toward 5th grade students’ understanding on sciences based on motivation in padang - Desty Ayu Anastaha; Yanti Fitria; Irdamurni Irdamurni (Jurnal Aplikasi IPTEK Indonesia, 2018)
This study aims to explain (1) Differences in understanding the concept of science students who taught using Inquiry Strategy with students who were taught using Conventional Strategy on science learning in class V SD, (2) Differences understanding of science concept between high motivation students with Low motivation on science learning in class V SD, and (3) Differences of interaction between learning strategy with motivation in influencing understanding of science concept in class V SD Gugus 1 Kecamatan Padang Barat. The  population  consisted  of  all  the  fifth  grade  students  at Kecamatan Padang Barat in the school year 2016/2017. The sample size was 60 students. The data in this study consisted of (1) the data on the students’ learning motivation, (2) the data on comprehension of science. The data were analyzed using descriptive statistics and 2x2 factorial Anova. From the results of this research, it can be concluded that (1) (there was a difference on concept of science understanding between students’ taught by using Inquiry learning and those who were taught by using conventional technique), (2) there was different on sciences understanding between high motivation and low motivation students and (3) there was no significant interaction between teaching approach and motivation influencing concept of sciences understanding.